Atopic Dermatitis Treated Safely with Dupilumab during Pregnancy: A Case Report and Review of the Literature - Yolanka Lobo; Ruby C. Lee; Lynda Spelman (Karger Publishers, 2021)
Dupilumab is currently the only biologic treatment approved for moderate-to-severe atopic dermatitis. Though limited, available clinical data describing dupilumab use in pregnancy have not identified a drug-associated risk of major birth defects, miscarriage, or adverse maternal or fetal outcomes. Systemic treatment in pregnant women with atopic dermatitis is currently restricted to corticosteroids, cyclosporine A, and azathioprine. Atopic dermatitis often has a deleterious course in pregnancy which can cause substantial distress and significantly impact on global health and quality of life. We report a case of severe atopic dermatitis treated safely with dupilumab during pregnancy with no adverse maternal or fetal outcomes observed. Our case highlights that dupilumab use in pregnancy has its place but should always be preceded by careful assessment of the risks and benefits. Clinicians are encouraged to enroll their patients in relevant pregnancy registry studies to monitor outcomes in women exposed to dupilumab during pregnancy and lactation.